Oxygen Reduction Reaction on Nitrogen and Cobalt Modified Silicon Carbide Derived Carbon in Acidic Media. (19th June 2018) - Teppor, Patrick; Jäger, Rutha; Härk, Eneli; Joost, Urmas; Tallo, Indrek; Paiste, Päärn; Kirsimäe, Kalle; Lust, Enn
Abstract : Cobalt and nitrogen type oxygen reduction reaction (ORR) catalysts were synthesized via a simple solution-based method using a silicon carbide derived carbon as the support, a cobalt complex salt and different nitrogen precursors, namely 2, 2'-bipyridine and 1, 10-phenanthroline, as activator sources. According to the electrochemical measurements in acidic media, modification of the carbon support with cobalt and nitrogen increased the half-wave potential value of the oxygen reduction reaction by around 440 mV. The ORR stability of both materials was additionally studied in a 144 hour test and the half-wave potential values decreased by 90 mV and 130 mV for Co-Phen/C and Co-Bipyr/C, respectively.